Continuing challenges of primary neuroendocrine tumours of the thymus: A concisereview. Issue 12 (December 2022) - Lau, Joel; Ioan Cvasciuc, Titus; Simpson, Duncan; C de Jong, Mechteld; Parameswaran, Rajeev
Abstract: Primary neuroendocrine tumours of the thymus (NETTs) are exceedingly rare tumours, usually presenting around mid-life, which have a propensity towards males and smokers. They are seen more often in those with MEN-1, but multiple different genetic mutations have been found to be involved in the tumorigenesis of NETTs. Histologically, NETTs are classified according to number of mitoses, the presence of necrosis, and the presence or absence of small cell features. NETTs display a wide spectrum of behavior, and they can be incidentally found on chest imaging, on screening in MEN-1, or present with symptoms of local compression. Advanced disease and paraneoplastic syndromes are common. CT-, PET/CT-, MRI-scans, and somatostatin receptor scintigraphy are the imaging modalities of choice both for the initial assessment as well as for monitoring after treatment. For patients with localized disease, complete surgical resection with lymphadenectomy provides the best chance of long-term, disease-free survival, and can be achieved through either an open or thoracoscopic approach. While chemotherapy-regimens based on platinum, taxane, and temozolomide are used most often, the optimum chemotherapy regimen in the adjuvant and palliative settings remains unclear, as does the role of radiotherapy. Ongoing research on the most effective use of somatostatin analogues, peptide receptor radionuclide therapy (PPRT), kinase inhibitors and immunotherapy in patients with other types of advanced neuroendocrine tumours may lead to further treatment options for NETTs in the future.